Enhancing Investment Inclusion via the Optimal Crowd-Financing Model for Retail Sukuk Instruments - Toyibatussalamah; Ali Mahmud; Fidyah Arini Kusuma Wardhani; Gjosphink Putra Umar Sakka; Wa Ode Irma Sari (Perspectives on Advanced New Generations of Global and Local Economic Horizons, 2025)
The purpose of this study is to develop and empirically validate an optimal crowd-financing model aimed at boosting retail investor participation in sukuk instruments, addressing significant constraints in the retail sukuk market due to structural, psychological, and technological hurdles. Using a mixed-methods approach, primary data was gathered from 300 active retail investors (aged 18–45) and 15 key stakeholders in Indonesia via purposive sampling through a structured survey and in-depth interviews. The quantitative data was analyzed using Structural Equation Modeling (SEM). The model shows strong explanatory power ($R^2=0.68$), confirming that accessibility, technological ease, Shariah compliance, and investor trust are crucial drivers of inclusion. Key findings recommend reducing minimum investment amounts, improving FinTech usability, ensuring transparent Shariah governance, and providing targeted investor education. Regulatory harmonization and blockchain innovations are identified as vital for addressing operational challenges. In conclusion, this research provides a cohesive, actionable framework for regulators and issuers to achieve sustainable sukuk market growth and deepen financial inclusion in emerging economies. Future studies should explore the socio-cultural dynamics of sukuk adoption.